Keratinocyte growth factor 1, fibroblast growth factor 2 and 10 in the healing tympanic membrane following perforation in rats - Santa Maria, P.; Redmond, S.; Atlas, M.; Ghassemifar, Reza (2011)
The aim of this study was to provide a transcriptome profile of Keratinocyte Growth Factor (KGF)-1, Fibroblast Growth Factor (FGF) 2 and FGF10 (KGF2) in the healing rat tympanic membrane (TM) over 7 days and an immunohistochemical account over 14 days following perforation. KGF1, FGF2, and FGF10 play important roles in TM wound healing. The tympanic membranes of rats were perforated and sacrificed at time points over a 14-day period following perforation. The normalized signal intensities and immunohistochemical protein expression patterns at each time point for KGF1, FGF2, and FGF10 are presented. The primary role of both KGF1 and FGF2 appeared to be in the proliferation and migration of keratinocytes. Whereas the role of KGF1 appeared to be exclusively concerned with increased proliferation and migration at the perforation site, the continued expression of FGF2, beyond perforation closure, suggested it has an additional role to play. FGF10 (KGF2), whilst possessing the highest sequence homologous to KGF1, has a different role in TM wound healing. The effect of FGF10 on keratinocytes in wound healing appeared to emanate from the connective tissue layer. © 2010 Springer Science+Business Media B.V.